MENELUSURI ASAL MUASAL LAHIRNYA ORKES KOLINTANG MINAHASA - Dinar Sri Hartati (SELONDING, 2012)
Kolintang is amusical genre. It is well known as a musical ensemble came from Minahasa, in North Celebes. But, many people do not know yet about the history of how this music was built, And why its construction and instrumens composition are as like as this time. This article describes about the contextual backround on how this music was builtand who are and the agents as the maker. Keywords: Kolintang, History, Minahasa